Oracle database 12C Oracle RMAN backup and recovery - Freeman, Robert G., 1965-; Hart, Matthew (Matthew Sheridan) (Online access with DDA: Askews (Maths), 2016)
'Oracle Database 12c RMAN Backup & Recovery' explains how to generate reliable archives and carry out successful system restores. You will learn to work from the command line or GUI, automate the database backup process, perform Oracle Flashback recoveries, and deploy third-party administration utilities.